Poronienie i ciąża obumarła w aspekcie prawa - udział położnej w opiece nad pacjentką w sytuacji utraty ciąży = Miscarriage and pregnancy degenerated in terms of law - part midwife in the care of the patient in case of pregnancy loss - Sabina Katarzyna Stadnicka; Agnieszka Bień; Paulina Gdańska; Joanna Piechowska (Kazimierz Wielki University, 2016)
Stadnicka Sabina Katarzyna, Bień Agnieszka, Gdańska Paulina, Piechowska Joanna. Poronienie i ciąża obumarła w aspekcie prawa - udział położnej w opiece nad pacjentką w sytuacji utraty ciąży = Miscarriage and pregnancy degenerated in terms of law - part midwife in the care of the patient in case of pregnancy loss. Journal of Education, Health and Sport. 2016;6(9):379-390. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.62008 http://ojs.ukw.edu.pl/index.php/johs/article/view/3841       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 06.09.2016.     Poronienie i ciąża obumarła w aspekcie prawa - udział położnej w opiece nad pacjentką w sytuacji utraty ciąży Miscarriage and pregnancy degenerated in terms of law - part midwife in the care of the patient in case of pregnancy loss   Sabina Katarzyna Stadnicka, mgr położnictwa, doktorantka, Katedra i Zakład Pielęgniarstwa Pediatrycznego, Wydział Nauk o Zdrowiu Uniwersytetu Medycznego w Lublinie Agnieszka Bień, dr n. med., adiunkt, Zakład Podstaw Położnictwa, Wydział Nauk o Zdrowiu Uniwersytetu Medycznego w Lublinie Paulina Gdańska, mgr psychologii, I Katedra i Klinika Położnictwa i Ginekologii Warszawskiego Uniwersytetu Medycznego Joanna Piechowska, mgr położnictwa, doktorantka, Zakład Podstaw Położnictwa, Wydział Nauk o Zdrowiu Uniwersytetu Medycznego w Lublinie         Streszczenie Niekorzystne zakończenie ciąży ma charakter niezwykle złożony i delikatny. Utrata ciąży na skutek poronienia jest wydarzeniem biomedycznym wywierającym ogromny wpływ na funkcjonowanie psychiczne. Nowe Rozporządzenie Ministra Zdrowia z dnia 1 grudnia 2015r. wprowadza dokładnie określone standardy postępowań okołoporodowych w opiece nad pacjentkami w sytuacji niepowodzeń położniczych. Celem publikacji jest pokazanie istotności wprowadzenia standardów. Odpowiedni przekaz niepomyślnych wiadomości, poprawna komunikacja a także udzielenie wsparcia może załagodzić psychologiczne skutki niepomyślnej sytuacji. Słowa kluczowe: ciąża, poronienie, strata, przepisy prawa, zdrowie psychiczne     Abstract Unfavorable termination of pregnancy is a very complex and delicate. Pregnancy loss due to miscarriage is an event biomedical exerting a huge influence on the functioning of mental health. The new Minister of Health of 1 December 2015. introduces precisely defined standards proceedings perinatal care for female patients in an obstetric failures. The aim of the publication is to show the significance of the introduction of standards. The corresponding message bad news, the correct communication and assistance can alleviate the psychological effects of unfavorable situation. Key words: pregnancy, miscarriage, loss, law, mental health